MPLEMENTASI PASAL 280 KITAB UNDANG UNDANG HUKUM PERDATAATAS HAK WARIS ANAK LUAR KAWIN - I Kadek Adi Surya (Jurnal Ilmiah Raad Kertha, 2023)
Children born out of wedlock are children born to a woman who does not have legal marriage ties with a man who has instilled a child in her womb, the child does not have a perfect position in the eyes of the law like legitimate children in general. The child out of wedlock is a term that refers to Article 43 paragraph (1) of the Marriage Law, which states that: Children born out of wedlock only have civil relations with their mothers and their mothers' families. The Constitutional Court through Decision Number 46/PUU-VIII/2010 stated that Article 43 paragraph (1) of the Marriage Law is conditionally unconstitutional insofar as this paragraph is interpreted as eliminating civil relations with men which can be proven based on science and technology and/or other evidence according to law has blood relations as the father. Inheritance Law is closely related to Family Law, because all inheritance matters regulated by law are based on blood-related relations by marriage. Inheritance law as a field that is closely related to family law is a classic example in the condition of a heterogeneous Indonesian society (Unity in Diversity) that it is impossible to force unification. The type of research used in this journal is to use a legal basis or the opinion of scholars, the results of the research include, among other things, children out of wedlock who are not recognized will not cause legal consequences in inheritance, because children out of wedlock are not recognized either by their mothers or by their parents. his father could not inherit the property left by his parents. Meanwhile, an illegitimate child who is recognized as valid either by the mother or by the father or by both of them will cause legal consequences in inheritance, Article 280 of the Civil Code states that recognition made to a child out of wedlock will result in a legal relationship between the child and the father and Mothers who acknowledge and children out of wedlock, both voluntarily and compulsorily acknowledged, are included in the first class of ab-intestato heirs because children out of wedlock are children of the heir, even though by way of recognition. However, the position of a child out of wedlock is not the same as the position of a legitimate child in inheritance because a legitimate child can inherit the inheritance of his parents without regard to the presence of the next class of ab-intestato heirs